Second Language Learning in a Multilingual Environment: Displaced Ukrainian Primary School Students’ Experiences of Learning German in Switzerland - Abramicheva, Olena (Journal of Vasyl Stefanyk Precarpathian National University, 2025)
Drawing on international pedagogical discourse on multilingual learning contexts, extensive research on second language acquisition and learning, and our previous research on Ukrainian refugee perspectives on primary school in German-speaking Switzerland, the author examines experiences of learning German as a second language by displaced Ukrainian children in Swiss primary schools. The longitudinal study allowed for the exploration of dynamics of German language acquisition by displaced children in conditions of full immersion in the target language environment and the identification of factors influencing their second language learning and performance. The exploratory study was carried out within the framework of a qualitative methodology with data collection through semi-structured interviews, narrative inquiry, and participant observations as research tools. Data analysis revealed that the effects of the second language learning environment are the strongest compared to other learner-external factors and vary within the research period. Placed in regular Swiss classes to ensure their non-segregated mainstream education in the host country, displaced children are exposed to two languages at school – Standard German (the official language of school) and the Swiss dialect, which is spoken by the local Swiss population in the German-speaking part of Switzerland and, correspondingly, by the local school community. Although perceived in the early stages of inclusion as a major hindrance to meaningful learning and communication with peers, over time, the diglossic school setting has proven to be a path to displaced learners’ sociolinguistic competence and integration in the local school. Also, the learning of German by displaced children in conditions of full immersion is greatly influenced by the availability of structured forms of learning, exposure to interactional activities with native speakers in informal settings, and the target language socialization contexts.